2022
DOI: 10.1039/d2gc00680d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free, redox-neutral, and visible light-triggered coupling of CO2 with epoxides to cyclic carbonates at atmospheric pressure

Abstract: The metal-free, redox-neutral, photocatalyzed insertion of CO2 into epoxides to give cyclic carbonates under visible light irradiation at atmospheric pressure is demonstrated. In our approach we used 9,10-anthraquinone in conjunction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Next, an aliquot of the resulting mixture was taken and analyzed by NMR spectroscopy (Bruker Avance III 400 MHz) with CDCl 3 as a solvent. Thus, the NMR yield is calculated from the integration of the peaks characteristic of the mesitylene, epoxy and carbonate C β –H (methine) at the 1 H NMR spectrum of this crude sample and comparison to published spectra. It should be noted that the selectivity toward cyclic carbonate formation was >99%, and no other byproducts were detected.…”
Section: Methodsmentioning
confidence: 99%
“…Next, an aliquot of the resulting mixture was taken and analyzed by NMR spectroscopy (Bruker Avance III 400 MHz) with CDCl 3 as a solvent. Thus, the NMR yield is calculated from the integration of the peaks characteristic of the mesitylene, epoxy and carbonate C β –H (methine) at the 1 H NMR spectrum of this crude sample and comparison to published spectra. It should be noted that the selectivity toward cyclic carbonate formation was >99%, and no other byproducts were detected.…”
Section: Methodsmentioning
confidence: 99%
“…All calculations unless otherwise specified were carried out using the Gaussian 09 suite of programs . DFT calculations of geometries, energies, and vibrational frequencies in this paper were performed with the M06-2X functional , using the 6-311+G­(d,p) basis set for C, H, O, N, F, and K atoms and the SDD effective core potential with an extra f -polarization function ( f = 0.289) for the I atom, the level of which was tested to better describe the free energies of CO 2 cycloaddition to epoxides. Vibrational frequency calculations were carried out at the same theory level to identify all stationary points as minima (with zero imaginary frequency) or first-order saddle points (with one imaginary frequency). The intrinsic reaction coordinate calculations , were performed to verify that the structures/energies to be used were in fact from the true transition states.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In general, photothermal catalysis can be sorted into thermal-assisted photocatalysis, photo-assisted thermocatalysis, and photo-thermal co-catalysis. [10][11][12][13][14] While numerous studies about CO 2 cycloaddition have reported on pure thermo- [15,16] and photocatalysis, [17] only a few have explored the photothermal catalytic processes. [18][19][20] With a unique electronic structure and unsaturated coordination environment, single-atom catalysts usually show high photothermal catalytic performance in CO 2 cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%